Students' language learning style preferences at Pham Hong Thai High School, Hanoi: a case study = Sở thích học ngoại ngữ của sinh viên trường THPT Phạm Hồng Thái, Hà Nội: điển cứu. M.A Thesis Linguistics: 60 14 10 - Thái, Thị Phương Nga (2017)
M.A. Thesis English Teaching Methodology -- College of Foreign Languages. Vietnam National University, Hanoi, 2009